PENGARUH FAKTOR-FAKTOR SUMBER STRES (STRESSORS) DI TEMPAT KERJA TERHADAP STRAIN FISIOLOGIS DAN PSIKOLOGIS KARYAWAN PT. ADYA GRAHA SURABAYA - Nuraini, Dewi (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2007)
Research utilizes regression analysis to analyse stress's causal factor influence (stressors) at work to physiological strain (effect stress) and psychological strain employee PT. Adya Graha Surabaya.. Stress is not settling to evoke social phenomena or can also at conceive of physiological phenomena, psychological and behavioural its response one different for one any one. To the effect of observational it is subject to be test how stress causal factor influences, in this case is work condition, work, work group, organization and career that are measured by use of scale likert to physiological strain and psychological strain , and to know how many influence that variable are influence physiological strain and psychological strain. Result this research points out that individual's there are three influential variable significant to physiological strain which are, environmentally physical, work and organization. Meanwhile influential variable significant to psychological strain just exists one variable which is, work. Key word: physiological strain, psychological strain, work condition, work, work group, organizational, careers.